If Going From Free Markets to Free Markets Is the Science Based Approach: What is Then the Model Structure, Price Structure, Choice Structure and the Knowledge Structure and Related Gaps of the 2012 Paradigm Shift From Perfect Traditional Market to Perfec - Muñoz, Lucio (IJRDO - Journal of Business Management, 2017)
When paradigm shifts they shift from free market to free market or from perfect market to perfect market to maintain or respect the theory-practice consistency principle. The necessary and sufficient condition for a perfect shift to take place is the internalization of externality costs in the pricing mechanism of the market. And when a shift takes place four things are expected to happen at the same time: a model structure shift, a price structure shift, a choice structure shift, and a knowledge structure shift creating in the process model, price, choice, and knowledge gaps. In 2012 there was a paradigm shift from perfect traditional markets to perfect green markets, which raises a very important question: If going from free markets to free markets is the science based approach: What is then the model structure, price structure, choice structure and the knowledge structure and related gaps of 2012 paradigm shift from perfect traditional market to perfect green market thinking?. The main goal of this paper is to provide an answer to this question